Hematopoietic pre‐B cell leukemia transcription factor interacting protein is overexpressed in gastric cancer and promotes gastric cancer cell proliferation, migration, and invasion. Issue 10 (25th September 2015) - Feng, Yingying; Li, Ling; Zhang, Xiaomei; Zhang, Yunjing; Liang, Yingchun; Lv, Jinjing; Fan, Zhongyi; Guo, Jing; Hong, Tian; Ji, Beibei; Ji, Quanbo; Mei, Guohui; et al.
Abstract : Hematopoietic pre‐B cell leukemia transcription factor interacting protein (HPIP) has been shown to play an important role in the development and progression of some cancers. However, the role of HPIP in gastric cancer (GC) is unclear. Here, we show that HPIP is upregulated in most GC patients and promotes GC cell proliferation, migration, and invasion. In GC patients, HPIP positively associates with tumor size and nodal metastasis, and negatively associates with tumor differentiation. Hematopoietic pre‐B cell leukemia transcription factor interacting protein increases GC cell proliferation through activation of G1 /S and G2 /M cell cycle transitions, accompanied by a marked increase of the positive cell cycle regulators, including cyclin D1, cyclin A, and cyclin B1. Hematopoietic pre‐B cell leukemia transcription factor interacting protein enhances GC cell migration and invasion, and modulates epithelial–mesenchymal transition, which plays a key role in cancer cell migration and invasion. These data underscore the critical role of HPIP in GC cell proliferation and progression and suggest that HPIP inhibition may be a useful therapeutic strategy for GC treatment. Abstract : HPIP is overexpressed in gastric cancer and promotes gastric cancer cell proliferation, migration and invasion.